2013
DOI: 10.1063/1.4840935
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation in dielectric fluid in inhomogeneous pulsed electric field

Abstract: This paper proposes a method for studying the early stages of the cavitation development in arbitrary, non-stationary conditions. This method is based on the comparison of the results of calculations in the framework of a theoretical model of the liquid dielectrics motion in a strong non-uniform electric field and experiments with controlled parameters. This approach allows us to find the critical negative pressure, at which cavitation begins to develop, and to determine the values of the constants in the clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…where V and t are the volume and the duration of the measurement, respectively.  is the kinetic prefactor, which depends on the theoretical model used in [1][2][3][4][5][6]. For example, in [3,6], it was accepted that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where V and t are the volume and the duration of the measurement, respectively.  is the kinetic prefactor, which depends on the theoretical model used in [1][2][3][4][5][6]. For example, in [3,6], it was accepted that…”
Section: Introductionmentioning
confidence: 99%
“…The critical pressure, at which cavitation occurs can be easily estimated by equating the exponential factor in (6) . Accounting for pre-exponential factor in (6) has practically no effect for the estimation (7).…”
Section: Introductionmentioning
confidence: 99%
“…Such mechanism of а secondary cavitation ruptures generation should lead to the appearance of chains of nanopores, aligned along the electric field lines, in which the breakdown may be developed. Furthermore, this mechanism is an explosive, because the rate of cavitation ruptures generation depends strongly on the absolute value of the electrostrictive negative pressure [27], and does not depend on the rate of expansion and merging of nanopores. …”
Section: "Cavitation" Breakdown In the Liquidmentioning
confidence: 99%
“…Note that only the appearance of ruptures in the fluid is not sufficient for the development of * m.n.shneider@gmail.com breakdown, since at the radius of the nanopore [27], an electrostatic pressure arises in the cavitation pore, due to the distortion of its main electric field, which exceeds the Laplace pressure. In the paper [28], the estimate of the rate of the nanopores expansion is made, and it was shown that three characteristic regions are arising in the vicinity of a needle electrode.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Electrostriction plays an important role also in the manipulation of microdroplets and liquid surfaces by laser pulses [4,5]. These effects are not limited only to laser radiation, but can be achieved also by the discharge of electrodes [6,7,8].…”
Section: Introductionmentioning
confidence: 99%